2018
DOI: 10.1159/000491756
|View full text |Cite
|
Sign up to set email alerts
|

Antidermatophytic Activity and Skin Retention of Clotrimazole Microemulsion and Microemulsion-Based Gel in Comparison to Conventional Cream

Abstract: Aim: Antifungal activity, skin permeation and skin retention of water-in-oil microemulsion (ME) and microemulsion-based gel (MBG) containing clotrimazole (CTZ) were evaluated in comparison to a conventional CTZ cream. Methods: CTZ-ME and CTZ-MBG containing 1% w/w of CTZ were produced. Antifungal activity against Trichophyton mentagrophytes was assessed by the agar diffusion method. Pig skin was used in the in vitro penetration study using modified Franz diffusion cells. Drug amounts which permeated into the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Sampling intervals were 1, 2, 3, 4, 5, 6, 7, 8, 12, 16, 20, and 24 h. Results showed that clotrimazole was not permeated through the skin up to 24 h following the permeation studies from all the tested formulations. Similar results were observed in reports published in literature with clotrimazole microemulsions [43], clotrimazole loaded three-dimensionally-structured hybrid vesicles [17], and roxithromycin ufosomes [18]. As most of the fungal infections are localized on the surface of the skin, systemic bioavailability of clotrimazole is not required.…”
Section: Resultssupporting
confidence: 88%
“…Sampling intervals were 1, 2, 3, 4, 5, 6, 7, 8, 12, 16, 20, and 24 h. Results showed that clotrimazole was not permeated through the skin up to 24 h following the permeation studies from all the tested formulations. Similar results were observed in reports published in literature with clotrimazole microemulsions [43], clotrimazole loaded three-dimensionally-structured hybrid vesicles [17], and roxithromycin ufosomes [18]. As most of the fungal infections are localized on the surface of the skin, systemic bioavailability of clotrimazole is not required.…”
Section: Resultssupporting
confidence: 88%
“…For example, studies have verified that the colloidal drug delivery system, including microemulsions, nanoemulsions, and micelles; vesicle drug delivery system, including liposomes, alcohol liposomes, liposome-like structures, and transporters; and nanoparticle drug delivery system, including solid lipid nanoparticles and nanostructured liposomes, promote skin penetration and retention of drugs. [10][11][12][13] Polymer micelles are colloidal solutions with core-shell structures that are formed by the self-assembly of amphiphilic copolymers above the critical micelle concentration. They are often used as carriers of water-insoluble drugs and have good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic peak of the aromatic group (C–H stretching) at 3167 cm –1 is indicated, while the peak at 1593 cm –1 showed the aromatic group (CC stretching). The peak at 1570 cm –1 corresponds to CN stretching, while the peak at 1040 cm –1 showed C–H stretching as shown in Figure S10 (Supporting Information) . The FTIR spectra of CTZ-free μE, CTZ-μE, CTZ-free μEG, and CTZ-μEG for both formulation A and formulation B are given in Figure .…”
Section: Resultsmentioning
confidence: 96%
“…The peak at 1570 cm −1 corresponds to CN stretching, while the peak at 1040 cm −1 showed C−H stretching as shown in Figure S10 (Supporting Information). 61 The FTIR spectra of CTZ-free μE, CTZ-μE, CTZ-free μEG, and CTZ-μEG for both formulation A and formulation B are given in Figure 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%